2021
DOI: 10.21037/atm-21-1863
|View full text |Cite
|
Sign up to set email alerts
|

BMAL1 attenuates intracerebral hemorrhage-induced secondary brain injury in rats by regulating the Nrf2 signaling pathway

Abstract: Background: Intracerebral hemorrhage (ICH) is a severe cerebrovascular disease with high morbidity and mortality rates. Oxidative stress and inflammation are important pathological mechanisms of secondary brain injury (SBI) after ICH. Brain and muscle Arnt-like protein 1 (BMAL1), which forms the core component of the circadian clock, was previously shown to be involved in many diseases and to participate in oxidative stress and inflammatory responses. However, the role of BMAL1 in SBI following ICH is unknown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
(85 reference statements)
1
10
0
Order By: Relevance
“…miRNAs have also been found to influence Nrf2. The miRNA-155 inhibitor antagomir-155 increases the expression of brain and muscle Arnt-like protein 1 (BMAL1) and activates the Nrf2 signaling pathway to attenuate neuroinflammation, oxidative stress, and neuronal death after ICH in rats ( 137 ). In addition, the miRNA-139/Nrf2/NF-κB axis may play a critical role in monomethyl fumarate’s (MF) role in conferring alleviation of neuroinflammation and oxidative stress, particularly considering that miR-139 overexpression reduces nuclear NF-κB levels and elevates nuclear Nrf2 levels in SH-SY5Y cells compared to controls and that levels of all three molecules are altered by MF treatment ( 138 ).…”
Section: Mechanism Of Microrna In Modulating Neuroinflammation After Ichmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs have also been found to influence Nrf2. The miRNA-155 inhibitor antagomir-155 increases the expression of brain and muscle Arnt-like protein 1 (BMAL1) and activates the Nrf2 signaling pathway to attenuate neuroinflammation, oxidative stress, and neuronal death after ICH in rats ( 137 ). In addition, the miRNA-139/Nrf2/NF-κB axis may play a critical role in monomethyl fumarate’s (MF) role in conferring alleviation of neuroinflammation and oxidative stress, particularly considering that miR-139 overexpression reduces nuclear NF-κB levels and elevates nuclear Nrf2 levels in SH-SY5Y cells compared to controls and that levels of all three molecules are altered by MF treatment ( 138 ).…”
Section: Mechanism Of Microrna In Modulating Neuroinflammation After Ichmentioning
confidence: 99%
“…In addition, NF-κB also contributes significantly to the regulation of post-ICH neuroinflammation by miRNAs. The Nrf2 and PI3K/AKT pathways have been reported by several studies to be targeted by miRNAs, thus affecting the course of neuroinflammation after ICH ( 135 , 137 ). Of note, there are contradictory results concerning the effects of several miRNAs on their targets, such as miR-144 modulation of the mTOR autophagic pathway and of neurological functions ( 95 , 96 , 142 ).…”
Section: Prospects For New Therapiesmentioning
confidence: 99%
“…Previous study show that Bmal1 directly regulates the Nrf2 signaling pathway by binding to its response element E-box ( Early et al, 2018 ). Recently, Gong et al (2021) found that miRNA-155 could negative regulate BMAL1 in mRNA level. Inhibiting miRNA-155 can promote the expression of BMAL1 and further activate the Nrf2 signaling pathway to attenuate brain injury induced by ICH.…”
Section: Regulation Of Nuclear Factor Erythroid-2-related Factor 2 Pa...mentioning
confidence: 99%
“…Brain and muscle Arnt-like protein 1 is a transcription factor and a principal driver of the molecular clock in mammals ( Gong et al, 2021 ). BMAL1 forms a heterodimer with CLOCK, which binds to E-box sites that have locations throughout the genome; this binding influences the rhythmic expression of various clock-controlled genes ( Early and Curtis, 2016 ).…”
Section: Regulation Of Nuclear Factor Erythroid-2-related Factor 2 Pa...mentioning
confidence: 99%
See 1 more Smart Citation